(untitled) (LACCEI, 2024)
The growth kinetics of polyacrylamide hydrogel beads in different aqueous glycerin solutions and its dependence on the concentration of glycerin in solution was studied. The influence of the confinement imposed by an (adjustable) wall allowing the hydrogel to grow freely only up to fixed openings of 5 and 10 mm was also analyzed. The equilibrium sizes of the hydrogels do not depend on the glycerin concentration, except above 50% (w/w) but they do change with the imposed confinement, obtaining smaller values. On the other hand, the growth kinetics is slower with increasing glycerin concentration. This growth kinetics is accurately described, at initial and intermediate times, by an empirical power law widely used in the literature. In free growth experiments, the curves collapse into universal kinetics when time is rescaled using the viscosity of the solution. This suggests that the growth kinetics under these conditions is only limited by viscous transport. Whereas, when there is imposed confinement, this also influences the kinetics and no universal curve for growth kinetics is obtained.